Mentors and student-teachers "lesson studying" in initial teacher education. Issue 2 (11th April 2016) - Cajkler, Wasyl; Wood, Phil
Abstract : Purpose: – The purpose of this paper is to study an adapted version of lesson used with mentors and student-teachers in a one-year initial teacher education (ITE) programme for prospective teachers of geography and modern languages. In partnership with eight secondary schools, the effectiveness of the lesson study cycle was evaluated as a vehicle for exploration of approaches to aid student-teacher learning during school placements. Design/methodology/approach: – In total, 12 lesson study case studies were completed and analysed. Findings: – Three principal findings emerged: first, most collaborating mentors and student-teachers reported that they engaged in a reflexive process, exploring the complexity of teaching, each learning more about the characteristics of teaching; second, in cases where collaboration allowed student-teachers a degree of autonomy, lesson study provided a collaborative scaffold for understanding the complexity of teaching, contributing to professional development along a continuum which the authors tentatively term "pedagogic literacy"; third and less positively, some mentors struggled to shed the shackles of traditional roles, dominating the discourse as advice-givers so that a traditional "parallel" approach to mentoring continued. Originality/value: – The work expands the experiential base of lesson study efforts in ITE in the UK and elaborates a view of teacher learning that challenges reductive approaches to the preparation of new teachers. For the first time, it presents student-teacher and mentor perspectives on the use of lesson study in teaching practice in England.